Analysis of the Complexities in the Water-Energy-Food Nexus: Ghana's Bui Dam Experience - Siakwah, Pius; Torto, Obodai (Frontiers in Sustainable Food Systems, 2022)
The quest to improve the mired development challenges of developing economies at a global scale have in recent years constituted policy imprimatur of development discourse, including the role of national and local resources. “Nexus” is an ultra-prioritized integrative global development approach. It denotes connection(s) linking two or more phenomena or variables. It is therefore not surprising to witness of-the-moment approaches such as the development-security nexus, migration-development-security nexus, and water-energy nexus, among others. Particularly relevant to this article is the water-energy-food (WEF) nexus as an integrative strategy to tackle prosaic issues of industrialization, poverty reduction, food security, and ecological sustainability. Adopting a qualitative methodological approach, the article studies the Bui dam to elucidate how the nexus operates in a complex and tense environment. The central argument is that most analyses of WEF interventions, particularly from the mainstream development literature rarely interrogate complex politics of interest amongst the trident sectors (water, energy, and food). The dominant studies tend to dwell on the technical or instrumental aspects. But an understanding of the complex relationships at play needs a critical approach. Our key argument is that the WEF nexus is prominently embedded in complex historical systems that tend to counter-balance the hyper-deductive projected costs and benefits. It is critical to view the relations amongst the WEF from a non-linear and realistic perspective. WEF as an embodiment of a complex system helps us to understand the multi-level, contradictory, and diverse interests at play within, between, and across the systems. Even though the nexus operations on an assumption of seamless collaborative relations among and between institutions, agencies, and actors in the policy and program implementation space, an analysis of the Bui project in Ghana shows tensions, side-lining, and inter-role conflicts among the actors, where the energy sector actors weigh power and resources over other institutions and actors in the space to drive the nexus.